Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Noires sous surveillance : esclavage, répression et violence d'État au Canada - Maynard, Robyn (Mémoire d'encrier, 2018)
La vérité a souvent un goût amer. Nous ne savons comment accepter nos histoires. Faut-il s’en tenir aux faits et dire la vérité ? Cet ouvrage monumental si richement documenté est précieux, il nous tire de l’oubli et du silence. Que savons-nous de l’esclavage au Canada ? Que savons-nous de la répression exercée sur les femmes et les hommes noirs ? Que savons-nous du racisme systémique ? Que savons-nous de la détresse des Autochtones, des sans-papiers, des personnes réfugiées ? Enfin fort peu… Parce que l’État construit et déconstruit les récits à travers les institutions. Les citoyen.ne.s sont ainsi condamné.e.s à reproduire une histoire qui nous échappe.
Donné en lecturecours FEM1000: "La misogynoire au Canada" p.173-178 Donné en lecture au cours POL4212: « Chapitre 5 : La Mysoginoire ».
Keywords: EDI; afro-féminisme; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; fem3300; féminismes noirs; histoire; justice sociale; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences

La pensée feministe noire : savoir, conscience et politique de l'empowerment - Hill Collins, Patricia (Les éditions du remue-ménage, 2016)
Confrontées à une société sexiste et raciste qui leur impose des images stigmatisantes d’elles-mêmes, les femmes noires des États-Unis n’en ont pas moins une longue histoire de résistances. Dans cet essai incontournable enfin traduit en français, Patricia Hill Collins nous offre une synthèse impressionnante de cette tradition d’oppression et de militantisme. La pensée féministe noire puise autant dans la littérature, les récits de vie, l’histoire militante, la philosophie sociale et politique, la sociologie critique que dans la culture populaire. Elle nous incite à penser non seulement les oppressions enchevêtrées, mais aussi les luttes passées et à venir. Ce livre donne accès à un savoir profondément ancré dans l’expérience irréductible des Africaines-Américaines; un savoir essentiel pour qui se préoccupe de justice sociale et pour un féminisme véritablement inclusif.
Le Chapitre 5 "Le pouvoir de l’autodéfinition" a été donné en lecture au cours POL4212.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; com5170; cours; cycles supérieurs; discipline; fem1000; fem3300; fem7000; féminismes noirs; har4600; incontournable; intersectionnalité; justice sociale; militance; pol4212; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis

Quand projet d’immigration rime avec inscription dans les cours de francisation. La trajectoire langagière de neuf immigrantes scolarisées dans la région montréalaise - Ralalatiana, Michela Claudie; Vatz-Laaroussi, Michèle (Diversité urbaine, 2016)
Pour les nouveaux arrivants, le fait d’apprendre la langue du pays d’accueil les aide dans leur processus d’intégration. C’est le cas des femmes immigrantes du Québec, bien que plusieurs autres défis les attendent. Malgré tout, elles sont travaillantes et motivées dans cet apprentissage. Cet article présente une recherche portant sur la trajectoire langagière de neuf femmes immigrantes inscrites dans un programme de francisation au Québec. Par la démarche de la biographie langagière, des entrevues semi-dirigées et un journal d’apprentissage tenu durant quatre mois, ces neuf femmes scolarisées et inscrites à des cours de français à temps complet ont été interrogées sur leurs contacts avec la langue française, les langues parlées en classe au Québec et à la maison, leurs réseaux d’amis et leurs activités sociales. Globalement, elles sont proactives, s’ajustent au lieu où elles se trouvent, à l’Autre et aux enjeux du moment.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; inégalités; justice sociale; montréal; outils; pour des recherches en milieux de pratiques; premier cycle; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; soc1061; sociologie; systèmes d'oppressions; thématiques; travail

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Daniel Guérin et le discours militant sur l'homosexualité masculine en France (années 1950-années 1980) - Marchant, Alexandre (Revue d’histoire moderne & contemporaine, 2006)
Daniel Guérin (1904-1988), intellectuel marxiste et militant anarchiste, est un révélateur pour mesurer certaines transformations des représentations sociales de l’homosexualité en France, des années 1950 aux années 1980. Guérin incarne le passage d’un univers de discours (au sens de modèles de communication) à un autre,du légalisme arcadien à la perspective révolutionnaire du FHAR;de la discrétion à la politisation. Il a développé une pensée théorique originale de l’homosexualité, en rabattant celle-ci sur une bisexualité originelle. Sa réflexion sur les transformations sociales et historiques de l’identité homosexuelle inscrit la question des identités sexuelles dans une perspective nominaliste. Dans les années 1950 et 1960, les écrits de Guérin traitent de la répression de l’homosexualité en France. L’auteur donne également un éclairage particulier à la question de la révolution sexuelle des années 1970. Ses interventions littéraires ou publiques, dont la forme varie selon les contextes et les époques, ont encouragé la revendication politique d’une homosexualité stigmatisée juridiquement et réprimée policièrement.Néanmoins,de la fin des années 1970 à sa mort, il a durement critiqué l’essentialisation progressive de l’homosexualité au rang de marqueur identitaire.
Keywords: 1900-1999; EDI; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours militant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; marxisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Sains et saufs : petit manuel de lutte contre l'homophobie à l'usage des jeunes - Dorais, Michel; Verdier, Éric (VLB, 2005)
Section: 166, [10] pages ; 19 cm
Keywords: EDI; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; identités LGBTQIA2+; intervention sociale; justice sociale; premier cycle; psy4910; pédagogie; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences

Black feminist thought: Knowledge, consciousness, and the politics of empowerment - Hill Collins, Patricia (Routledge, 2000)
A revision of a hugely successful book; this is the 'bible' of contemporary black feminist thought and is widely cited and taught as a seminal text. Completely up-to-date with recent events, trends in popular culture, current events, and politics.
Première publication : 1990 Édition 10e anniversaire
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; discipline; féminismes noirs; incontournable; intersectionnalité; justice sociale; militance; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis